Kenaikan Tarif PPN 12%: Dampak dan Kontroversi di Tengah Masyarakat - Jingga Lini Feburinta; Muhammad Fachri; Erinaldi; Chely Aninthya (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines the impact of the increase in the Value Added Tax (VAT) rate from 11% to 12% implemented by the Indonesian government in 2025. The research employs secondary data analysis from various official and reliable sources to assess the effects of this policy on household consumption patterns, inflation, and the resulting social responses. The findings indicate that the VAT increase places pressure on the purchasing power of lower- and middle-income groups, leading to a decline in the consumption of non-essential goods. The policy also triggered public protests, prompting the government to revise the regulation by limiting the 12% VAT rate to luxury goods only. This study concludes that the VAT increase presents a dilemma between fiscal needs and public welfare; therefore, responsive mitigation measures and effective public communication are necessary to maintain socio-economic stability.